Dissecting The Toto Myths, Tales, and Legends: Review of Oral Stories of the Totos by Ketaki Datta - Sreetanwi Chakraborty (Litinfinite, 2022)
For author Ketaki Datta who has compiled and edited Oral Stories of the Totos, the meaning of fiction acquires not this abstract meaning. It is a consummate appraisal of the lives lived, the social, religious, economic aspects of the Toto community, a small tribe living in the Alipurduar district of West Bengal. She takes a profound interest in the cultural production and amalgamation of their artistic forms, linguistic diversities and community cohesion that makes them very different from the other neighbouring people included as part of the Koch, the Mech, the Bhutanese tribes or even from the Rajbongshis to a large extent. As we examine the introduction and then each of the chapters very carefully, we find how there is the reference to a ‘cultural osmosis’ by the author, and intercultural weddings have given rise to an exchange of cultural diversity from Nepal. The balancing act happens when the Totos have to retain their old socio-cultural milieu and yet be open and adaptive to the newer, incoming alternative ideas from Nepal and other neighbouring countries